The Effect of Combination Ovariectomy and D-galactose Administration on Alzheimer's Animal Model (Baghdad Science Journal, 2022)
Background and purpose: Animal model helps researchers to evaluate new treatment plan for human and understand pathological mechanism involved in a development of disease. The use of rats as an animal model for Alzheimer's research has become a favorite among researchers. Rats are capable in mimicking Alzheimer disease due to their intelligence and quick adaptation to nature. At present there are several methods that can be used to induce Alzheimer's animals, but each method has advantages and disadvantages. We need to learn other methods that can provide many advantages and few disadvantages. The Amyloid-beta 42 (Aβ-42) and Reactive Oxygen Species (ROS) are thought to play an important role in the pathology of Alzheimer’s disease. This study aims to investigate whether ovariectomy and D-galactose can be an effective method for inducing Alzheimer's animal models.This was an experimental study with control group design. Twelve female Sprague Dawley rats were involved and grouped into two groups. Control group who did not undergo ovariectomy and the experiment group underwent ovariectomy and was given intraperitoneal D-galactose 500 mg/kg.bw. Amyloid beta-42 plasma and Y-Maze test were conducted after 6 weeks. The results showed that the experiment group has lower mean Y-Maze score (42,79 ± 6,97) compared with control group (74,27 ± 4,01) and the Amyloid-beta 42 plasma was higher in the control group. In conclusion ovariectomy and D-galactose are proven to induce cognitive decline and higher plasma Amyloid-beta 42 in the Alzheimer’s animal model.